FACTORS AFFECTING RETURN ON ASSETS OF US TECHNOLOGY AND FINANCIAL CORPORATIONS - John Francis Diaz; Rudresh Pandey (Jurnal Manajemen dan Kewirausahaan, 2019)
The research studies the relationship between eight firm-specific factors on the profitability of U.S. technology and financial firms. The study used multiple linear panel regression models, namely, ordinary least squares (OLS), fixed effects (FE) and random effects (RE) models. Empirical findings show that return on equity ratio is negatively related with return on assets (ROA), while return on sales ratio has positive relationship with profitability for both technology and financial firms. On one hand, current ratio has a positive relationship with the profitability of the financial firms, while there is negative relationship for technology firms. Lastly, size has positive relationship with the profitability for technology firms. This study provides renewed perspectives in creating suitable strategies to controlling factors that maximizes profitability for both US publicly-listed technology and financial companies.